Structuring international economic cooperation - Boyd, Gavin (Pinter, 1991)
Argues the need for economic co-operation between the major industrialized democracies, because interdependencies link advanced market economy states so that the policies of each affect the inflation and employment rates and trade flows of other countries. Strategies for co-operation are discussed.